From Red Cliffs to Chosin : the Chinese way of war - Pangelinan, James G. (Pickle Partners Publishing, 2014)
This monograph examines Chinese warfare and suggests that three and a half millennia of Chinese military history have produced a distinctive and enduring Chinese Way Of War. While the art and science of war in China have evolved considerably throughout its history, the characteristics and philosophies of its style of warfare contain some propensities that endure from antiquity to the present. They are: The Chinese military orientation focuses more on the strategic and operational levels of war than the tactical. The Chinese prefer strategic maneuver warfare to attritional or other forms of warfare. Chinese warfare emphasizes the importance of shaping operations, the arrangement of the conditions of the war, campaign, or battlefield in one's favor before initiating combat. Finally, deception and unorthodox warfare play a leading role in Chinese martial philosophy and conduct of war. These four propensities of the Chinese way of war are general trends that emerge when the entire span of Chinese warfare is broadly considered. Rooted in the philosophy and theories of the great military classics of ancient Chinese, these propensities provide continuities in the war fighting styles, traditions, and preferences of Chinese armies throughout history. While none of the four propensities of Chinese warfare are practiced by China alone, when aggregated they form a broad approach to war fighting that is unlike that of any other country in the world. The distinctiveness of the Chinese way of war is a product of China's unique cultural traditions, religious and social philosophies, and historical evolution.